Los Valores y su Incidencia en el Estado Conductual de los Adolescentes del Hogar Marcelino Champagnat de la Ciudad de Loja y la Intervención del Trabajador Social - Iñiguez Delgado, Liliana Estefanía (2016)
For many teens, a life with values may sound dull and deprived of freedom but in reality is quite the opposite Sheila Morataya (1999) states that adolescence "are the years where we decide the values which give meaning to our life." Inadequate practice of values is a reality that exists in today's society, because there is no adequate training at home on the basis of the example of his family, which is why easily influence external factors such as: friends and the environment in which man develops, causing major problems and barriers to social coexistence. Due to inadequate practice of values in our society, there is increasingly less tolerance, more aggressiveness, disrespect, lack of solidarity, among others, a problem that has been observed in adolescents living in the Home Marcellin city of Loja. This research is focused incident known as the inadequate practice of values in the behavioral state of adolescents Home Marcellin. To which the objectives enabled the design of a proposed social action entitled "Enjoy your youth practicing values." As well as theoretical and scientifically support the research problem categories for testing with empirical information; in the same way to determine causes and effects of the lack of values, which generate negative consequences reflected in the behavior of adolescents, inappropriate behavior that affects interpersonal relationships. The main findings that influenced the improper practice of values of adolescents were: economic problems, neglect, family neglect, lack of affection, indifference, orphanhood, which directly affect the behavioral state of adolescents reflected in: insecurity, aggression, discrimination and uncommunicative teenagers. To carry out field research non-probability sampling taking as example the population of 12 teenagers living at Home and 7 administrative Marcellin working in the same was chosen. In the methodology the scientific method and its subsidiary as an empirical method, inductive, analytic-synthetic and statistical method, same that contributed 5 to the literature review and explain the research question is based, as affects the inadequate practice of values in the behavioral state Home adolescent Marcellin, through the categories of cause and effect that are implicit in the development of the research process. Among the techniques used: observation that allowed visualize the problem of higher incidence; the survey of stakeholders, who provided information for the development of research and interview to deepen a little more about the object of study. As a basis tool field notebook was used to take note of relevant data found during the research process. As mentioned above it is concluded and recommended that the proposal be implemented in order to contribute to the practice of values to improve behavior status of adolescents Home Marcelino Champagnat.